The Protective Effects of Zeaxanthin on Amyloid-β Peptide 1–42-Induced Impairment of Learning and Memory Ability in Rats - Li, Xiaoying; Zhang, Ping; Li, Hongrui; Yu, Huiyan; Xi, Yuandi (Frontiers in Behavioral Neuroscience, 2022)
Background and Objectives: Zeaxanthin (ZEA) as one of biologically active phytochemicals presents neuroprotective effect. Since ZEA may play its anti-oxidative role in neurodegenerative diseases including Alzheimer’s disease (AD), we hypothesized cognitive defect could be prevented or deferred by ZEA pre-treatment. Methods and Study Design: All rats were randomly divided into four groups (control, Aβ1-42, ZEA, and ZEA+Aβ groups). Learning and memory ability of rats, cerebrovascular ultrastructure changes, the redox state, endothelin-1 (ET-1) level and amyloid-β peptide (Aβ) level in plasma and the Aβ transport receptors which are advanced glycation end products (RAGE) and LDL receptor related protein-1 (LRP-1) and interleukin-1β (IL-1β) expressions in cerebrovascular tissue were measured in present study. Results: The escape latency and frequency of spanning the position of platform showed significant differences between Aβ group and ZEA treatment groups. ZEA could prevent the ultrastructure changes of cerebrovascular tissue. In addition, ZEA also showed the protective effects on regulating redox state, restraining ET-1 level and maintaining Aβ homeostasis in plasma and cerebrovascular. Moreover, the disordered expressions of RAGE and LRP-1 and IL-1β induced by Aβ1-42 could be prevented by pre-treatment of ZEA. Conclusions: ZEA pre-treatment could prevent learning and memory impairment of rats induced by Aβ1-42. This neuroprotective effect might be attributable to the anti-oxidative and anti-inflammatory effects of ZEA on maintaining redox state and reducing Aβ level through regulating Aβ transport receptors and inflammatory cytokine of cerebrovascular tissue.